MANAJEMEN PEMBELAJARAN PENDIDIKAN KARAKTER PADA SD NEGERI BANYUBIRU I KECAMATAN DUKUN, MUNTILAN, KABUPATEN MAGELANG (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The main purpose of this study described the implementation of management of the learning caracter education in The State of Banyubiru 1 Primary School of The Dukun District Of The Muntilan, Magelang, Center of Java Province.The research used the qualitative approach and the subjects were teachers, the principal, the students, the supervisors, and the parents. The data were collected by observation, interview, and documentation methods. The research found that : (1) In principle, the teachers of the state of Banyubiru 1 Primary School of The Dukun District Of The Muntilan, Magelang, Center of Java Province Province implemented the learning caracter education by integrated with the learning material, (2) Unoptimally in the implementation of the caracter education learning management caused by the lacks of views and knowlege of the teachers about character values and how to integrate in the learning management and about the evaluation system. (3) The awareness of the teacher on character values as a educational basis and instrument act as supporting factors in implementing and developing the character education learning management. (4) Base on the research results it suggested that the knowledge, view, and abilities of teachers about character values and how to implement it in the character education learning management and the evaluation sytem should be improved.